2003
DOI: 10.2190/v6b4-pqaw-ttv0-cjcu
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Freshmen Retention of Orientation Course Content: Proposed Persistence Model

Abstract: This study examined the effectiveness of different topics/activities included in a freshman orientation course in enhancing the students' perception of their successful adjustment to college life and the impact of these subjects on the student level of persistence. The results support the Tinto stage model of persistence since the elements of the orientation course most highly correlated to persistence were topics and activities dedicated to: 1) the development of strong social networks (with both faculty and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 13 publications
0
17
1
Order By: Relevance
“…The results of an empirical study, conducted by Davig andSpain (2003-2004) to identify those topics/activities in a freshman seminar that were most effective, found… …support [for] the Tinto stage model of persistence since the elements of the orientation course most highly correlated to persistence were topics and activities dedicated to: 1) the development of strong social networks (with both faculty and students) and 2) integration into the institution. Results also suggest that certain topics/activities should be included in orientation courses in order to help students become more effective in dealing with their external relationships as specified in the Astin attrition model.…”
mentioning
confidence: 99%
“…The results of an empirical study, conducted by Davig andSpain (2003-2004) to identify those topics/activities in a freshman seminar that were most effective, found… …support [for] the Tinto stage model of persistence since the elements of the orientation course most highly correlated to persistence were topics and activities dedicated to: 1) the development of strong social networks (with both faculty and students) and 2) integration into the institution. Results also suggest that certain topics/activities should be included in orientation courses in order to help students become more effective in dealing with their external relationships as specified in the Astin attrition model.…”
mentioning
confidence: 99%
“…Studies conducted on first-year seminars reached similar conclusions in 2005, finding that first-year seminars provide positive and statistically significant advantages to students who enroll in such courses ( Porter & Swing, 2006). Numerous studies have indicated that first-year seminar participation promotes persistence into the second year and over longer periods of time ( Davig & Spain, 2004;Porter & Swing, 2006;Wild & Ebbers, 2002;Zimmerman, 2000). Other findings indicated that first-year seminars positively affect grade point averages, student involvement in campus activities, and utilization of campus resources (Barefoot, 1993a; Davis, 1992;Fidler & Hunter, 1989;Hunter, Skipper, & Linder, 2003;Hyers & Joslin, 1998;Maisto & Tammi, 1991;Zeidenberg et al, 2007).…”
Section: Community College Attrition and First-year Seminarsmentioning
confidence: 90%
“…Hoachlander, Sikora, and Horn (2003) noted that fostering student success in the first year is pivotal for student persistence. One of the most pervasive programs implemented to improve student persistence is the first-year orientation seminar (Davig & Spain, 2004;Fidler & Hunter, 1989;Gordon & Grites, 1984;Hunter, Skipper, & Linder, 2003;Hyers & Joslin, 1998;Starke, Harth, & Sirianni, 2001;Stovall, 2002;Zeidenberg, Jenkins, & Calcagno, 2007).…”
Section: Commitment To Completementioning
confidence: 99%
See 2 more Smart Citations